Proposed Improvement of Factory Layout for KSF Industry Sdn Bhd using Flexsim Software - Nooranizam, Nur Fatin Farzana; Salwa Mahmood (Progress in Engineering Application and Technology, 2024)
Effective layout planning is crucial for optimizing production efficiency even when equipment and product design are high quality. Kia Shing Foodtec Sdn Bhd, a manufacturer of dried vegetables and fruits, faces challenge due to an irregular facility layout, leading to inefficiencies such as cross-movement from the cutting station to the transfer product station and excessive distances between interconnected stations. This project aims to propose an improvement layout for Kia Shing Foodtec Sdn Bhd, comparing time and cost between the current and proposed layouts using Flexsim software. A flow  process chart was employed to examine the sequence of operations, focusing on material flow movements. Flexsim software was utilized to analyze processor staytime, total output, average content, bottlenecks, processor operation efficiency, and financial data. The current layout’s total running time was 1118.05 minutes, whereas the proposal layout’s running time was reduced to 1095.02 minutes. Cost analysis fir a 1-day process showed a reduction from RM1,678.80 to RM1,562.43 in the proposed layout. The percentage improvements in cost and time were 6.93% and 2.6% respectively. The findings indicate that the proposed layout significantly enhances time and cost efficiency. Consequently, the developed layout is recommended for implementation at Kia Shing Foodtec Sdn Bhd to optimize their production process.